30 Best foot forward? successful multi-disciplinary novel treatment of fixed equinovarus dystonia in three patients with functional neurological disorder. (28th May 2019) - Cary, Isabel; Nadler, Martine; Dilley, Mike; Symeon, Chris
Abstract : Objective/Aims: Functional Neurological Disorder (FND) affects 10-30% of neurology outpatients. Symptoms commonly include sensory, motor and cognitive changes without structural nervous system damage. Fixed equinovarus dystonia (FEVD) of the foot and ankle is a common feature of FND characterised by plantar flexion and inversion of the foot which cannot be corrected passively. This prevents weight-bearing often causing permanent wheelchair dependence. FEVD correction is necessary for patients to walk again. Consensus opinion is that invasive treatments are ill-advised and potentially detrimental in patients with FND. However, we have developed a novel approach that may challenge this opinion for a specific patient group, combining invasive treatments and neuropsychiatry interventions. Methods: A patient-led, goal oriented, multidisciplinary approach guided treatment. Treatments included functional electrical stimulation, botulinum toxin, tibial nerve block, serial casting and surgical intervention as an adjunct to specialist physiotherapy, occupational therapy, psychology. Standardised outcome measures of gait and mobility, balance, anxiety and depression were performed on admission and discharge. Patient consent was obtained for photo and video recording. Results: For three, wheelchair-dependent patients with FND and FEVD admitted to The Wolfson Neuro-rehabilitation Centre for 12-24 week inpatient treatment, our approach resulted in two walking independently and one with supervision. Care needs were reduced and wheelchair dependence was eliminated. Patients reported improvement in independence and quality of life with one patient returning to part- time employment as a PA (See Table 1 ). Conclusions: With selective psychological and medical screening, invasive treatment for FEVD in FND patients delivered through a careful, stepwise treatment pathway produced excellent results for this subgroup of patients. Though such interventions are usually avoided for patients with FND, there may be a subgroup of patients for whom they remain useful as a treatment adjunct in order to maximise rehabilitation and functional outcomes.